On-surface isostructural transformation from a hydrogen-bonded network to a coordination network for tuning the pore size and guest recognition - Zhou, Dong-Dong; Wang, Jun; Chen, Pin; He, Yangyong; Wu, Jun-Xi; Gao, Sen; Zhong, Zhihao; Du, Yunfei; Zhong, Dingyong; Zhang, Jie-Peng (Chemical science (Cambridge), 2020)
Rational manipulation of supramolecular structures on surfaces is of great importance and challenging. We show that imidazole-based hydrogen-bonded networks on a metal surface can transform into an isostructural coordination network for facile tuning of the pore size and guest recognition behaviours. Deposition of triangular-shaped benzotrisimidazole (H 3 btim) molecules on Au(111)/Ag(111) surfaces gives honeycomb networks linked by double N-H N hydrogen bonds. While the H 3 btim hydrogen-bonded networks on Au(111) evaporate above 453 K, those on Ag(111) transform into isostructural [Ag 3 (btim)] coordination networks based on double N-Ag-N bonds at 423 K, by virtue of the unconventional metal-acid replacement reaction (Ag reduces H + ). The transformation expands the pore diameter of the honeycomb networks from 3.8 Å to 6.9 Å, giving remarkably different host-guest recognition behaviours for fullerene and ferrocene molecules based on the size compatibility mechanism. A hydrogen-bonded network on a Ag(111) surface can transform into an isostructural Ag( i ) coordination network, giving drastically different host-guest recognition behaviours.